2021
DOI: 10.1007/s12291-021-00959-0
|View full text |Cite
|
Sign up to set email alerts
|

Klotho, BDNF, NGF, GDNF Levels and Related Factors in Withdrawal Period in Chronic Cannabinoid Users

Abstract: Klotho and neurotropic factors have recently been shown to be related to some psychiatric disorders and neurocognitive disorders, but there is no study on this issue within substance users. In this study, brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), glial derived neurotrophic factor (GDNF) and klotho serum levels of a patient group consisting of 27 chronic cannabis users according to the DSM-V and 27 healthy volunteers were compared, and their relationships with other the clinical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Several studies have tested this hypothesis by measuring serum BDNF levels in cannabis users with variable results [10,11,[16][17][18][19][20][21]. Therefore, the aim of this systematic review is to investigate and summarize the existing literature regarding the levels of BDNF in individuals with cannabis use disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have tested this hypothesis by measuring serum BDNF levels in cannabis users with variable results [10,11,[16][17][18][19][20][21]. Therefore, the aim of this systematic review is to investigate and summarize the existing literature regarding the levels of BDNF in individuals with cannabis use disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Following the full‐text review, 11 studies met the inclusion criteria and were included in the quantitative synthesis. A flow diagram illustrating the study selection process is presented in Figure 1 (Angelucci et al., 2008 ; Bayazit et al., 2019 ; Chagas et al., 2014 ; D'Souza et al., 2009 ; Jockers‐Scherubl et al., 2004 , 2006 ; Lisano et al., 2020 ; Miguez et al., 2019 ; Szabo et al., 2020 ; Toll et al., 2020 ; Yazici et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, younger addicts (aged 21-30 years) had higher Klotho level than older addicts (aged 31-40 years), but there was no significant difference in Klotho level between the age groups. Yazici et al in Turkey indicated a significant negative correlation between age and Klotho level among those with chronic cannabis use in the withdrawal period [23], which suggests the detrimental effect of cannabis on Klotho level in the body. According to our results, the serum level of Klotho was almost the same in male addicts and healthy men.…”
Section: Discussionmentioning
confidence: 99%